Ontogenetic changes in the morphology of Eharius chergui (Acari: Phytoseiidae) - Ma, Min; Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2018)
The morphological ontogeny of Eharius chergui (Athias-Henriot, 1960) is described in this paper based on laboratory-reared specimens originating from Marrubium vulgare L. (Lamiaceae) collected in North Island, New Zealand. Malformation was observed in the development of some idiosomal setae in some specimens and was suggested to be related to the host plant M. vulgare.